Upaya Peningkatan Pemahaman Teks Arab Pada Pembelajaran Maharah Al-Qiroah Melalui Media Quizizz - Halimatus Sa`diyah (Naskhi: Jurnal Kajian Pendidikan dan Bahasa Arab, 2023)
This research is related to the application of interactive quizzes through the Quizzz media in the learning of Maharah Al-Qiroah or reading skill. The purpose of this study is to increase students' understanding of Arabic texts in Al-Qiroah's Maharah learning through the application of interactive quizs with the media quizizz. This study includes classroom action research with two cycles and each cycle is applied to the preliminary stage, planning, action, observation and reflection. The subject of this study was 41 students of PS 2 at PKPBA (Special Program for Development of Arabic Language) UIN Maliki Malang in 2021. The data was obtained from the observation of the Al-Qiroah Maharah Learning Process, Documentation and Test in the Learning of Al-Qiroah Maharah. The results of this study indicate: (1) Increasing the average value and percentage of student learning completeness in the learning of Al-Qiroah Maharah, there is an increase from cycle I to cycle II, (2) Students have given a positive response to the use of the quiz Interactive Helper Media Quizizz in Learning Al-Qiroah Maharah. Thus, the application of an interactive quiz to the Quizizz media can increase students' understanding of Arabic texts in learning Al-Qiroah Maharah for students.